What is 4R nutrient stewardship? - Guodong Liu; Kelly Morgan; Yuncong Li; Lincoln Zotarelli; James DeValerio; Qingren Wang (EDIS, 2015)
A new and innovative approach to Best Management Practices for fertilizer application known as 4R nutrient stewardship is available, to ensure the environmental, social, and economical sustainability of commercial crop production. This 3-page fact sheet focuses on the basic concepts of the 4R nutrient stewardship principles for commercial crop production. Written by Guodong Liu, Kelly Morgan, Yuncong Li, Lincoln Zotarelli, James DeValerio, and Qingren Wang, and published by the UF Department of Horticultural Sciences, July 2015.